Fire-created habitats support large mammal community in a Mediterranean landscape - Soyumert, Anil; Ertürk, Alper; Tavşanoğlu, Çağatay (Springer Science and Business Media LLC, 2019)
Large mammals play significant roles in shaping the trophic structure of terrestrial ecosystems and affect the form of vegetation growth in many habitats. We studied large mammal community in a Mediterranean habitat mosaic generated by fires originally dominated by pine forests. We conducted camera-trapping surveys in three study sites with different fire histories, and we recorded eight large mammal species including brown bear (Ursus arctos), caracal (Caracal caracal), and wild goat (Capra aegagrus), which are of conservation importance. The mammal community found in the study sites was functionally diverse, including herbivores, omnivores, carnivores, seed dispersers, soil diggers, main preys, and top predators. The site burned 13 years ago had higher species richness than can be expected from a random pattern, but this was not the case in 30- and >40-year-old sites, showing the importance of relatively younger sites for large mammals. Eurasian badger had more probability to have more abundance in places with more open vegetation while wild goat had higher abundance in more dense vegetation. Young individuals of wild goat, brown bear, and wild boar were also detected in the study sites. The results indicate that burned habitats harbor a phylogenetically and functionally diverse large mammal community in landscapes originally dominated by Mediterranean pine forests. Therefore, these forests continue to retain importance for the large mammals after the fire, and burned habitats should be taken into consideration for the conservation and management plans together with mature forests in Mediterranean ecosystems.
Keywords: 13. Climate action; 14. Life underwater; 15. Life on land